Software Process and Product Measurement - Cuadrado-Gallego, Juan J. (Springer, 2017)
This volume is the post-proceedings of the IWSM-Mensura 2007 conferenceand consists of a set of 16 final papers selected from the conference. Each one ofthese papers has been thoroughly revised and extended in order to be acceptedfor this edition. The IWSM-Mensura Steering Committee is very proud to haveobtained the approval of Springer to publish the first edition of the joint con-ference post-proceedings in the prestigiousLecture Notes in Computer Sciences(LNCS) series and hope to maintain this collaboration for the future editions ofthe conference.